Cephalic to internal jugular vein bypass with external jugular vein conduit for rescue of a failing brachiocephalic arteriovenous fistula - Jordan Eng, BS; Dean Klinger, MD; Momodou L. Jammeh, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Central vein occlusion involving the subclavian or innominate veins is a common complication of hemodialysis access. This can lead to venous hypertension manifesting as severe extremity edema and insufficient clearance during dialysis. If left untreated, central venous occlusion may lead to access failure. Here, we present a case of subclavian vein occlusion on the ipsilateral side of a brachiocephalic fistula treated with cephalic vein to internal jugular vein bypass with external jugular vein conduit resulting in resolution of symptomatic venous hypertension and preservation of access for dialysis.